(untitled) (Economic Journal of Nepal, 2022)
The rate of return to education is considered as a measure of profitability. Getting confined to a particular course of study, it is well known that the number of student choosing management in masters is increasing every year in Nepal. This study attempts to estimate the private rate of return to MBA for individuals employed in development banks in Kathmandu Metropolitan City (KMC). A questionnaire survey was done to collect data from 164 MBA graduates working in development banks. Using the linear regression method, it is found that the rate of return to MBA for individuals employed at development banks in KMC is 23 percent. Further, male MBA graduates have been receiving 28 percent return to education and female MBA graduates have been receiving 22 percent. Hence, the findings suggest that undergraduates irrespective of their gender should pursue MBA for receiving higher return to investment in education.